Determination of heavy metals in skin‐whitening cosmetics using microwave digestion and inductively coupled plasma atomic emission spectrometry. Issue 5 (24th March 2017) - Alqadami, Ayoub Abdullah; Naushad, Mu; Abulhassan Abdalla, Mohammad; Khan, Mohammad Rizwan; Alothman, Zeid Abdullah; Wabaidur, Saikh Mohammad; Ghfar, Ayman Abdel
Abstract : In this study, the determination of noxious heavy metals, cadmium (Cd), bismuth (Bi), mercury (Hg), titanium (Ti), lead (Pb) and metalloid arsenic (As) in skin‐whitening cosmetics were examined using microwave digestion and inductively coupled plasma atomic emission spectrometry method. A complete digestion of cosmetics samples was achieved using a mixture of hydrofluoric acid/hydrogen peroxide/nitric acid. The quantification of the target compounds was done by standard addition method. The excellent quality parameters for instance, detection limits, As (4.6 ppb), Bi (7.9 ppb), Cd (0.45 ppb), Hg (3.3 ppb), Pb (3.8 ppb), Ti (4.3 ppb), linearity ( r 2 > 0.999) and run‐to‐run and day‐to‐day precisions with relative standard deviations <3% were obtained. The recovery rates for standard reference materials were found between 90 and 105%. The average concentration of heavy metals in cosmetics samples were in the range of 1.0–12.3 (μg g −1, As), 33–7097 (μg g −1, Bi), 0.20–0.6 (μg g −1, Cd), 0.70–2700 (μg g −1, Hg), 1.20–143 (μg g −1, Pb) and 2.0–1650 (μg g −1, Ti).